Demonstration of an ultraviolet stimulated Brillouin scattering pulse compressed hundred picosecond laser in LiB3O5 crystals. (11th July 2017) - Bai, Zhenxu; Wang, Yulei; Lu, Zhiwei; Jiang, Li; Yuan, Hang; Liu, Zhaohong
Abstract: A hundred picosecond ultraviolet (UV) laser is demonstrated with a pulse duration of less than 200 ps and peak power of 0.6 GW. With a hundred picosecond stimulated Brillouin scattering compressed pulse as the fundamental light, the UV output at 355 nm is obtained by extra-cavity sum-frequency-mixing in two LiB3 O5 crystals. Maximum UV energy was 100 mJ when the incident energy was 280 mJ, yielding an optical-to-optical efficiency of 35.7%. This result is of interest for the generation of high energy sub-nanosecond UV lasers which finds applications in shock ignition and industrial processing.